Root Canal Treatment and Esthetic Rehabilitation of Maxillary Central Incisor with Inclination Correction : A Case Report - Christina Mahardika; Qonitah Nur Aslamiyah (Universitas Muhammadiyah Semarang, 2026)
Introduction: The permanent maxillary central incisor is an anterior tooth with a high risk of developing cavities. If left untreated, cavities can progress to pulp and periodontal diseases, which are indications for endodontic treatment, specifically root canal treatment (RCT). In cases where extensive damage occurs after RCT, a full crown is needed to ensure restoration durability and aesthetics. This can be achieved using a fiber post and a porcelain-fused-to-metal (PFM) crown.Objective: to describe the root canal treatment and PFM crown restoration of tooth 21 with inclination correction to restore proper tooth function and achieve optimal aestheticsCase: A 48-year-old female patient visited RSGMP UNIMUS, complaining of a cavity in her upper left front tooth. The diagnosis for tooth 21 was Acute Apical Endodontitis (AAE) with pulp necrosis and normal apical tissue. The planned treatment included root canal treatment followed by PFM crown restoration with fiber-reinforced composite (FRC) post support.Outcome: The treatment results showed that the tooth functioned well and achieved good aesthetics.Conclusion: Root canal treatment and PFM crown restoration of tooth 21 with inclination correction showed a high success rate. The patient reported no complaints, the PFM crown remained intact without discoloration, adapted well to the surrounding tissues, had a negative palpation test, and showed no signs of traumatic occlusion.